The Di-Eu-Stress State Scale (DESS Scale): Development and Validation of a Scale Measuring State Distress and Eustress - Vikoler, Thomas; Kovács, Dániel; Traut-Mattausch, Eva (European journal of psychological assessment : official organ of the European Association of Psychological Assessment)
This paper describes the development and empirical validation of an instrument for measuring state distress and eustress, the Di-Eu-Stress State (DESS) Scale. In three studies, factorial validity (Study 1), construct validity (Study 2), predictability, and predictive validity (Study 3) were tested. We used data from 1,250 participants including 819 undergraduates and 431 employees from seven distinct cross-sectional and one ecological momentary assessment (EMA) sample. Study 1: Following exploratory factor analysis, two cross-sectional and one multilevel confirmatory factor analyses supported the resultant two-factor structure of distress and eustress across different contexts and measurement methods as well as against established holistic stress measures. Study 2: Construct validity of the DESS Scale was evaluated with convergent and discriminant measures as well as against established holistic stress measures. Study 3: Multilevel regression models showed the assumed results of demands and resources as antecedents of distress and eustress, respectively, as well as of the prediction of job and study satisfaction by distress and eustress. We discuss the key findings and limitations of each study as well as the practical implications of the DESS Scale in both the field of stress research and the vocational world. Suggestions for further validation of the DESS Scale are proposed.